Enforcement of Police Professional Ethics and Its Implications for Public Trust - Kimberly Fewsan; Meiraate Leos; Naomi Inly; Ramdhan Mahardika Nasyith; Telly Augustine; Triswer Triswer; Darren William; Yuni Priskila Ginting (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
The police profession carries the responsibility of law enforcement, maintaining public security and order, and providing protection and services to society. In performing these duties, members of the Indonesian National Police are required to uphold the professional code of ethics as a moral and professional foundation. Violations of police professional ethics not only undermine institutional integrity but also affect public trust in law enforcement institutions. This study aims to analyze the enforcement of police professional ethics and its implications for public trust. The research focuses on two main issues: (1) the extent to which the enforcement of the police code of ethics can create law-abiding, honest, and fair police officers; and (2) the efforts required to restore and strengthen public trust in the police institution following ethical violations. This study employs normative legal research using statutory, conceptual, and case approaches. The data were collected through a literature review of laws and regulations concerning the police professional code of ethics, decisions of the Police Code of Ethics Commission, court decisions, and relevant legal literature. The findings indicate that violations of police professional ethics constitute not only legal misconduct but also breaches of fundamental ethical principles, including integrity, accountability, honesty, and professionalism. The enforcement of ethical sanctions, including dishonorable discharge, reflects the institution’s commitment to maintaining ethical standards. However, weaknesses in internal supervision and institutional accountability remain significant challenges. Therefore, strengthening oversight mechanisms, enhancing transparency, and reforming organizational culture are essential to restoring and improving public trust in the Indonesian National Police.